The Effect of Climate Change on Variations in Dew Amount in a Paddy Ecosystem of the Sanjiang Plain, China. (28th February 2015) - Xu, Yingying; Yan, Baixing; Tang, Jie
Abstract : Due to global warming, a drying and warming trend has been observed over the last 50 years in the Sanjiang Plain of Heilongjiang Province, China, which could significantly affect the condensation of vapor in paddy ecosystems. Dew is a crucial factor in the water and nutrient cycling of farmland ecosystems, and it exerts an important influence on fertilization and other agricultural activities. In order to reveal the effects of global warming on dew variation in a paddy ecosystem, an in situ experiment was conducted in paddy fields in the Sanjiang Plain during the growing seasons of 2011 to 2013. Dew was collected and measured with a poplar stick. The results of correlation analysis between meteorological factors and dew intensity in the paddy ecosystem indicate that the dew point temperature and relative humidity significantly influenced the dew intensity. Based on synchronous meteorological data, a stepwise linear multivariation regression model was established to predict dew amount. The model successfully interpreted the relationship between simulated and measured dew intensity. The results suggest that a warmer and drier climate would lead to a reduction in dew amount because water cannot condense when relative humidity falls below 71%.